Literature Review: Analysis of Factors Influencing the Performance of Health Care Workers - Elfrida Jesika; Zairin Noor; Fauzie Rahman; Rosihan Adhani; Neka Erlyani (Indonesian Journal of Global Health Research, 2026)
Stunting is a chronic nutritional problem in toddlers influenced by various family factors. Maternal knowledge, parenting styles, and family income are thought to play a significant role in stunting. This study aims to synthesize scientific evidence regarding the relationship between these three factors and stunting in toddlers. This literature review analyzed case control articles published between 2022–2026 from PubMed, ScienceDirect, and Google Scholar based on inclusion criteria. The keywords used in the literature search for English-language journals included "health workers," "performance," "rewards," "leadership," "work skills," and "work environment." These keywords were combined using the Boolean operators AND and OR to obtain articles relevant to the research topic. The search was performed using the format "health workers" AND "performance" AND ("rewards" OR "leadership" OR "work skills" OR "work environment"). Meanwhile, similar keywords were used in national journals, namely "health workers," "performance," "rewards/awards," "leadership," "work skills," and "work environment," which were also combined using the Boolean operators AND and OR to broaden and focus the search results according to the research objectives. From 33,754 then narrowed down using keywords, 14 research articles were obtained. Fourteen articles were systematically reviewed. Most studies reported that low maternal knowledge increased stunting risk through inappropriate feeding practices, poor hygiene, and limited use of health services. Inadequate parenting practices significantly elevated stunting risk, particularly related to feeding, childcare, and growth monitoring. Low family income was also identified as a strong determinant because it affects the ability to provide nutritious food, proper sanitation, and access to healthcare. Some studies found no significant association due to other dominant variables such as maternal education and birth weight. These findings emphasize the importance of nutrition education for families alongside community health support delivered consistently through integrated programs at primary healthcare level and household environments sustainably and collaboratively across sectors locally. Knowledge, parenting, and income are interconnected factors influencing stunting, requiring comprehensive interventions.